Zakładnicy przeszłości? Lwowska Rada Obwodowa a stosunki ukraińsko-polskie .......... 241 - Kalytchak, Roman; Romanyuk, Nataliya (Tożsamość i pamięć : konteksty kulturowe i społeczne. Studia ukrainoznawcze, 2021)
HOSTAGES OF THE PAST? LVIV REGIONAL COUNCIL AND UKRAINIAN-POLISH RELATIONS Based on the analysis of official decisions, the study argues that being a representative body, the Lviv Regional Council actively strives to position itself as a speaker for the region’s interests in Ukrainian- Polish relations. The article also identifies key aspects of bilateral ties which are most relevant for regional deputies. The findings point that the historical narrative has been substantially determining the formation of the Regional Council’s vision of Ukrainian-Polish relations, particularly in the course of last four years.